Teaching With Technology In Classrooms: Implementing Blended Learning - Umi Kalsom, Masrom; Nik Aloesnita, Nik Mohd Alwi (Future Academy, 2018)
The technology advancement has encouraged more applications of online learning including blended learning. Public and private higher education institutions have implemented various steps to promote and encourage the incorporation of blended learning in the learning and teaching processes. Numerous benefits of blended learning are evident both in the area of education and corporate industry which includes accessibility, resources, cost effectiveness, flexibility and broader opportunities for learning. This paper aims at providing further insights into the existing claim of the benefits and challenges in employing blended learning at higher education institutions. These include, but not limited to, highlighting the potential of incorporating several blended learning tools into teaching and learning processes and discussion of innovative teaching approaches and strategies. Ultimately, the deliberation can assist instructors to select and to make informed-decisions of appropriate tools to be employed in order to achieve specific learning outcomes so that blended learning could be effectively implemented.